2016
DOI: 10.1007/s11274-016-2051-2
|View full text |Cite
|
Sign up to set email alerts
|

Illumina-based analysis of the rhizosphere microbial communities associated with healthy and wilted Lanzhou lily (Lilium davidii var. unicolor) plants grown in the field

Abstract: Lanzhou lily (Liliumdavidii var. unicolor) is the best edible lily as well as a traditional medicinal plant in China. The microbes associated with plant roots play crucial roles in plant growth and health. However, little is known about the differences of rhizosphere microbes between healthy and wilted Lanzhou lily (Lilium davidii var. unicolor) plants. The objective of this study was to compare the rhizosphere microbial community and functional diversity of healthy and wilted plants, and to identify potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 76 publications
4
34
1
Order By: Relevance
“…These discrepancies might be due to differences in crop types, continuous cropping years, and soil types. It has been reported that the changes in the diversity of soil bacterial community species differed greatly based on different years of continuous cropping [37], and plant species, plant genotypes and soil types had a certain impact on the structure of the soil microbial community [13,[38][39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These discrepancies might be due to differences in crop types, continuous cropping years, and soil types. It has been reported that the changes in the diversity of soil bacterial community species differed greatly based on different years of continuous cropping [37], and plant species, plant genotypes and soil types had a certain impact on the structure of the soil microbial community [13,[38][39].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the content of Lysobacter and Bacillus in the X18 rhizospheric soil were higher than those in Y138. Many studies showed that Bacillus may resist some soil-borne diseases [13,24,34]. The more content of Lysobacter and Bacillus would be more conducive to the growth of X18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shang et al showed that Fusarium , Rhizoctonia , Verticillium , Penicillium and Ilyonectria ( Neonectria ) in wilted samples may be pathogenetic root rot fungi (Shang et al, ). Und, Kotan, Sahin, and Ala, () showed that A. piechaudii , B. pumilus , Chromobacterium violaceum , E. intermedius , Erwinia rhapontici , Pantoea agglomerans , Pseudomonas aeruginosa , Pseudomonas huttiensis , Pseudomonas cichorii and Pseudomonas putida are possible foliar pathogens in pome fruits.…”
Section: Discussionmentioning
confidence: 99%
“…With the advantages of high-throughput, low price and short operation cycle, it has been widely used in the study of microbial community structure. Especially in the eld of medicinal plants, such as Panax ginseng [20], Panax notoginseng [21], Ajuga bracteosa [22], Origanum vulgare [23], Lilium davidii [24] and other plants are widely used.…”
Section: Introductionmentioning
confidence: 99%